2015
DOI: 10.1016/j.yrtph.2015.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccessibility of micron-sized powder particles of molybdenum metal, iron metal, molybdenum oxides and ferromolybdenum – Importance of surface oxides

Abstract: a b s t r a c tThe European chemical framework REACH requires that hazards and risks posed by chemicals, including alloys and metals, that are manufactured, imported or used in different products (substances or articles) are identified and proven safe for humans and the environment. Metals and alloys need hence to be investigated on their extent of released metals (bioaccessibility) in biologically relevant environments. Read-across from available studies may be used for similar materials. This study investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 66 publications
(72 reference statements)
3
9
0
Order By: Relevance
“…Dissolution rates of 0.6-18 µm/y and electrochemical corrosion rates of 5-13 µm/y were measured in various physiological solutions. These rates are in agreement with the corrosion rates for pure Mo of 0.32-9.47 µm/y reported by other groups [16][17][18][19][20] and close to the commonly referenced corrosion benchmark of 20 µm/y for a stent material [10]. The overall anodic dissolution reaction for molybdenum is:…”
Section: Introductionsupporting
confidence: 90%
“…Dissolution rates of 0.6-18 µm/y and electrochemical corrosion rates of 5-13 µm/y were measured in various physiological solutions. These rates are in agreement with the corrosion rates for pure Mo of 0.32-9.47 µm/y reported by other groups [16][17][18][19][20] and close to the commonly referenced corrosion benchmark of 20 µm/y for a stent material [10]. The overall anodic dissolution reaction for molybdenum is:…”
Section: Introductionsupporting
confidence: 90%
“…These metal compounds did not cause 8-nitroG formation, suggesting that metal impurities have no or weak ability to catalyze reactive species and cause DNA damage under the conditions used. It has been reported that iron and molybdenum were released from their particles in synthetic body fluid [ 51 ] and that nickel ions were released from nickel oxide nanoparticles in dispersion [ 52 ]. The bioavailability of metals used in this experiment appears to be comparable to those contained in MWCNT, although we cannot exclude the possibility that metal impurities remained insoluble in our experimental systems.…”
Section: Discussionmentioning
confidence: 99%
“…A 8 M NaOH (pH 13.6) was used as electrolyte in a volume of approximately 3 mL. Set-up details are given elsewhere (Morsdorf et al 2015). In brief, open circuit potential (OCP) measurements were performed in complete DMEM at pH 7.4 ± 0.1 for 48 h. Cyclic voltammetry (CV) measurements started from OCP (after 5 min stabilization), following a reduction at a rate of 0.0005 V/s to the lower water stability line (H 2 evolution peak) and an oxidation to the higher water stability line (O 2 evolution peak), or vice versa.…”
Section: Electrochemical and Surface Characterizationmentioning
confidence: 99%